Application of integrated method of HAZOP-AHP and fuzzy comprehensive evaluation in coal mine gas explosion accident. Issue 4 (March 2021) - Li, Dan; Cao, Qinggui; Wang, Junqing; Mi, Xin
Abstract: Hazard and Operability analysis (HAZOP), analytic hierarchy process (AHP) and fuzzy comprehensive evaluation methods are all important safety evaluation methods. For HAZOP analysis, the subjectivity is strong, the analysis process is complex, and accurate quantitative analysis cannot be performed. Proposed a safety evaluation method that combines HAZOP, AHP and fuzzy comprehensive evaluation, and integrated the three methods to make the HAZOP analysis method from qualitative analysis to qualitative and quantitative analysis, and improve the accuracy of risk identification. Finally, taking the gas explosion accident as an example, the above method is used to briefly analyze the gas explosion accident to verify the scientificity and feasibility of the method.